Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V - Suhaini, Siti Herli; Mustika, Dea (Cetta: Jurnal Ilmu Pendidikan, 2025)
Science education in elementary school is crucial for fostering students' scientific understanding and critical thinking skills. However, the low learning outcomes in science among fifth-grade students at SDN 001 Lubuk Terap, evidenced by scores below the Minimum Completeness Criteria (KKM) and less varied teaching methods, poses a significant problem. This study aimed to investigate the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model in improving students' science learning outcomes. Employing a Classroom Action Research (CAR) approach with two cycles at SDN 001 Lubuk Terap, this study involved 24 fifth-grade students. Data were collected through observation, tests, and documentation, then analyzed qualitatively and quantitatively. The results indicated a significant improvement in both teacher and student activities, as well as overall student learning outcomes. This was reflected by teacher and student activity percentages exceeding 90% in the "Very Good" category, and 100% of students achieving "Good" or "Very Good" in affective and psychomotor aspects. Furthermore, the average cognitive learning outcomes of students sharply increased from a "Sufficient" category in Cycle I to "Very Good" in Cycle II. Thus, this study concludes that the STAD cooperative learning model is highly effective in enhancing the science learning outcomes of fifth-grade students at SDN 001 Lubuk Terap, encompassing improvements in activities, affective, psychomotor, and cognitive learning outcomes. The STAD model is recommended for implementation by science teachers in other elementary schools to improve the quality of learning and student achievement.